2012
DOI: 10.1128/jcm.00775-12
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Vancomycin-Resistant Staphylococcus aureus, Vancomycin-Intermediate S. aureus, High Vancomycin MIC, and Outcome in Serious S. aureus Infections

Abstract: e Vancomycin has been used successfully for over 50 years for the treatment of Staphylococcus aureus infections, particularly those involving methicillin-resistant S. aureus. It has proven remarkably reliable, but its efficacy is now being questioned with the emergence of strains of S. aureus that display heteroresistance, intermediate resistance, and, occasionally, complete vancomycin resistance. More recently, an association has been established between poor outcome and infections with strains of S. aureus w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(86 citation statements)
references
References 31 publications
2
80
0
4
Order By: Relevance
“…Accumulating evidence of increasing resistance, unachievable pharmacokinetic/pharmacodynamic (PK/PD) targets and poorer outcomes challenges the suitability of the prime place of vancomycin in treatment regimens and guidelines [1][2][3][4][5][6].…”
Section: Use Of Vancomycinmentioning
confidence: 99%
“…Accumulating evidence of increasing resistance, unachievable pharmacokinetic/pharmacodynamic (PK/PD) targets and poorer outcomes challenges the suitability of the prime place of vancomycin in treatment regimens and guidelines [1][2][3][4][5][6].…”
Section: Use Of Vancomycinmentioning
confidence: 99%
“…Nevertheless, some data in the literature raise the possibility that factors in the invading bacterium may also contribute. Examination of the vancomycin minimal inhibitory concentration (MIC) value of MRSA strains that were recovered from patients with failed therapy showed that therapeutic failure correlated significantly with the vancomycin MIC value of the strains, even when this antibiotic was not used for therapy [11]. These data suggest that the vancomycin susceptibility profile of MRSA strains correlates with some aspects of the invasive potential of the bacteria.…”
Section: Introductionmentioning
confidence: 85%
“…Firstly, these high-V MIC isolates are likely to have undergone other molecular changes, so a more comprehensive genotypic and phenotypic analysis of these isolates will now be required to extend these findings [8,9]. Specifically, we did not use an established in vitro or in vivo endocarditis model, or a measure of growth rate, which we plan to do in future studies.…”
Section: Resultsmentioning
confidence: 99%
“…VISA and hVISA isolates have multiple phenotypic and metabolic differences compared with susceptible isolates, such as reduced autolysis and gradual thickening of the cell wall, changes in global gene regulators including down-regulation of agr, increased expression of surface adhesins that bind fibrinogen and fibronectin, and attenuated virulence [3,[8][9][10][11][12][13]. There is also clinical evidence that VISA and hVISA isolates are less virulent, with lower acute mortality and less shock reported in some studies [14,15].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation